Comparison of Transmittance and Reflectance Pulse Oximetry in Anesthetized Dogs - Nixdorff, Jan; Zablotski, Yury; Hartmann, Katrin; Dörfelt, Rene (Frontiers in Veterinary Science, 2021)
Objectives: The tongue is the standard site for placement of a pulse oximeter probe but is difficult to access during certain procedures such as dental and ophthalmic procedures and computerized tomography of the head. The aim of this study was to evaluate the performance of a new generation reflectance pulse oximeter using the tail and tibia as sites for probe attachment. Materials and Methods: A total of 100 client-owned dogs that underwent anesthesia for various reasons were premedicated with butorphanol (n = 50; 0.2 mg/Kg; group BUT) or butorphanol and dexmedetomidine (n = 50; 5 µg/Kg; group DEX), administered intravenously. Anesthesia was induced with propofol and maintained with sevoflurane. A transmittance pulse oximeter probe was placed on the tongue and served as the reference standard. A reflectance probe was randomly placed on the tail base or the proximal tibia, and the position changed after testing. Signals from three consecutive measurements were obtained at each position. Failure was defined as “no signal”, “low signal”, or a pulse difference >10/minute compared with the ECG heart rate. Data were analyzed using chi-square test, Wilcoxon matched-pairs signed-ranks test, and Bland-Altman analysis. P<0.05 was considered significant. Results: In both groups (BUT and DEX), failure rate was higher when the tibia and tail were used as probe sites compared with the tongue. In both groups, the failure rate was higher for the tibia than for the tail. Dexmedetomidine-induced vasoconstriction increased failure rate at all probe positions. Clinical Significance: The tail base, but not the tibia, is an acceptable position for reflectance pulse oximeter probes in dogs. The tongue remains the probe site of choice, if accessible.